2021
DOI: 10.13078/jsm.210007
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology, Diagnostics, and Treatment of Narcolepsy in Germany: The DORMIO Study

Abstract: Objectives: This study aimed to investigate the prevalence, incidence, and real-world diagnostic and treatment patterns, healthcare resource utilization (HCRU), and associated costs of narcolepsy in Germany. Methods: This study was based on German claims data (2013–2018). Any patient with at least two outpatient specialist diagnoses and/or one inpatient diagnosis of narcolepsy was eligible for inclusion. Three cohorts were specified: 1) narcolepsy-prevalent patients alive on July 1, 2017; 2) narcolepsy-inciden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Regional bias may be present, as AOK PLUS only insures patients from two German states (Saxony/Thuringia). However, in accordance with the German legal framework, health service reimbursement rules are identical across Germany, and previous studies have found no major regional differences in health care structures between Saxony/Thuringia and other German states [ 27 ].…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Regional bias may be present, as AOK PLUS only insures patients from two German states (Saxony/Thuringia). However, in accordance with the German legal framework, health service reimbursement rules are identical across Germany, and previous studies have found no major regional differences in health care structures between Saxony/Thuringia and other German states [ 27 ].…”
Section: Discussionmentioning
confidence: 84%
“…This retrospective claims data analysis used an anonymized dataset provided by the regional German statutory health insurance fund AOK PLUS, which covers 3.6 million people insured in Germany (regions of Saxony and Thuringia) [ 27 ]. In Germany, statutory health insurance is mandatory for individuals whose annual income is below a fixed limit, which applies to around 90% of the German population [ 28 , 29 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation